Programming Innovation: Art Residencies as a Model for the Sustainable Revitalization of Artisan Knowledge - Milutinovic, Lora (Taideyliopiston Sibelius-Akatemia, 2026)
While often examined through heritage studies or ethnographic perspectives, artisanship remains insufficiently theorized within art management, even despite the sector's increasing alignment with contemporary cultural production and the creative industries. The central aim of this thesis is to explore how contemporary art Residencies can act as models for Revitalizing heritage-based artisanal knowledge by Integrating innovation within structured cultural programs. This research suggests that art management may contribute to the sustainable future of artisanship by presenting artisan practices as living, relevant and sustainable creative skills which are not only a viable expression of cultural identity. Furthermore, art management practices can place artisan creativity within the CCI, offering artisans visibility on markets (such as design and contemporary art fairs) which would be excluded if the skills were only viewed in terms of heritage management. Ultimately, this thesis concludes that art Residency features such as the presence of an on-site master artisan, interaction with materials and sites of creation, room for experimentation and experiential learning, artisan communities and even interdisciplinary dialogues contribute to the Sustainability of artisan knowledge. Material, as proven to be the main axis of Theoretical investigations of artisanship - both past and present, as well as a crucial consideration for many artisans is Suggested as a conceptual point for planning art Residencies aimed at Revitalizing artisanship.
Keywords: innovations; art; artists; artist residences; creativity; artisans; art education; sustainable development; artistic research; residents; fi=kulttuurinen musiikintutkimus|sv=kulturell musikforskning|en=Cultural Study of Music|